Siemens AG Files Patent Application for Simulation System Method for Carrying Out a Simulation Guidance System and Computer Program Product (Indian Patents News, 2014)
According to the Controller General of Patents, Designs & Trade Marks, "The invention relates to a simulation system, in particular for a guidance system which controls a process (P) running in a technical system.